Positive association between stress hyperglycemia ratio and ICU mortality in patients with pulmonary embolism: A retrospective study - Jian Liao; Dingyu Lu; Maojuan Wang; Hanyang Yu (PLoS ONE, 2025)
Background Measurement of the Stress Hyperglycemia Ratio (SHR) aims to reduce the influence of prolonged chronic glycemic variables on stress hyperglycemia levels, which are associated with clinical outcomes. Nevertheless, the correlation between SHR and the risk of all-cause Intensive Care Unit (ICU) mortality in patients with pulmonary embolism(PE) remains unclear. Methods Data for this retrospective study were o btained from the MIMIC IV2.2 database. The participants were divided into four groups based on the SHR quartiles. The primary outcome measured was 28-day ICU mortality. We employed Cox proportional hazards regression analysis and restricted cubic splines to evaluate the correlation between the SHR and clinical outcomes in patients with PE. Results The study included 1185 patients, of which 53.3% were male. The rates of mortality observed in the ICU were 19.8%. By conducting multivariable Cox proportional hazards, it was determined that the SHR was independently associated with a heightened risk of 28-day ICU mortality (HR = 1.83 per 1-point increment, 95% CI = 1.07-3.13, p = 0.028).The analysis using restricted cubic splines showed that there was a consistent and gradually increasing risk of all-cause mortality as the SHR increased. This indicates that a higher SHR is associated with a higher risk of ICU mortality. Conclusions Elevated SHR was strongly linked to a higher risk of clinical outcomes in patients with PE. As an effective measure of stress hyperglycemia, SHR demonstrated superior performance in predicting risks compared to solely evaluating glycemia or HbA1c upon admission.